EVALUASI SISTEM PROSEDUR PEMBERIAN KREDIT DI LEMBAGA PERBANKAN - Nurdiyanto Yusuf (Jurnal Teknik dan Science, 2023)
Corporate governance in the world of economics is something that is considered as important as what happened in the state government. This study examines how the principles of Good Corporate Governance relate to credit granting procedures in banking institutions at PT. State Savings Bank (Persero) Tbk. This research is case study research conducted at a private company engaged in the banking sector in Indonesia. The aim of this research is to determine the relationship between the application of the principles of corporate governance (GCG) to credit granting procedures within the company. Corporate Governance as a set of rules that determines the relationship between shareholders, management, creditors, government, employees, and other internal and external stakeholders with respect to their rights and obligations, or in other words a system that directs and controls the company. Where there are five principles of Good Corporate Governance, namely: a) Information transparency, b) Accountability, c) Responsibility, d) Independence, e) Fairness. Data collection methods used in this research are interviews and analysis of company documents. The results of this study indicate that there is an important role between GCG implementation and credit granting procedures. The results of this study encourage and motivate companies so that GCG principles are used as a corporate culture.